Pengaruh Kelas Ibu Hamil terhadap Pengetahuan Kesehatan Kehamilan pada Ibu Hamil Primigravida di Wilayah Kerja Puskesmas Tanjung Karang - Bq. Nova Aprilia Azamti; Nurkarinah Nurkarinah; Wahyu Cahyono (LPPM STIKES Mataram, 2023)
Introduction: The problem that primigravida pregnant women often encounter is a lack of knowledge about pregnancy health due to lack of experience and lack of information about pregnancy health. One effort to increase knowledge among pregnant women is through classes for pregnant women. Based on the survey, data was obtained that only 60 pregnant women could take part in this activity (7.5%) with the number of primigravida pregnant women being 25 people (22.32%). Objective: to determine the influence of the Pregnancy Class for Pimigravida pregnant women on knowledge of pregnancy health in the Tanjung Karang Community Health Center working area. Method: The research design used was pre-experimental with a one group pre-post test design. The population in this study was 112 primigravida pregnant women with a total research sample of 30 primigravida pregnant women. Using purosive sampling techniques and data analysis using the paired T test with instruments using a questionnaire. Results: Knowledge about pregnancy health before treatment was in the quite good category, namely 19 respondents (63.33%), and after treatment in the good knowledge category there were 25 respondents (83.33%). The results of statistical tests using the T Paired test significance technique obtained a p value = 0.000 (< α = 0.05). Conclusion: that there is an influence of Pregnancy Class on pregnancy health knowledge among primigravida pregnant women in the Tanjung Karang Community Health Center working area